Foundations of maternal & pediatric nursing - White, Lois (Australia : Thomson Delmar Learning, 2005)
A textbook developed to cover the OBPedi/Materal-Child Health aspects of the practical/vocational nursing program curriculum. The text details the subjects of preconception education and care through pregnancy, birth process, newborn care, basics of pediatric care, infants with special needs, and common problems 1-18 years.
UNIT 1: NURSING CARE OF THE CLIENT: CHILDBEARING -- Prenatal care -- Complications of pregnancy -- The birth process -- Postpartum care -- Newborn care -- UNIT 2: NURSING CARE OF THE CLIENT: CHILDREARING: Basics of pediatric care -- Infants with special needs: birth to 12 months -- Common problems; 1-18 years
Includes bibliographical references and index.
Keywords: MATERNITY NURSING -- HANDBOOKS, MANUALS, ETC